Full Bridge LLC Resonant Three-Phase Interleaved Multi Converter for HV Applications - Salem M.; Ramachandaramurthy V.K.; Sanjeevikumar P.; Leonowicz Z.; Yaramasu V. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric frequency control; MATLAB; Natural frequencies; Zero voltage switching; Active switches; Interleaved converters; LLC resonant converter; Load variations; Magnetizing inductance; MATLAB /simulink; Three phase; Variable frequency control; Power converters